2012
DOI: 10.1249/mss.0b013e3182290371
|View full text |Cite
|
Sign up to set email alerts
|

A Protein–Leucine Supplement Increases Branched-Chain Amino Acid and Nitrogen Turnover But Not Performance

Abstract: Postexercise protein-leucine supplementation saturates BCAA metabolism and attenuates tissue damage, but effects on subsequent intense endurance performance may be inconsequential under conditions of positive daily nitrogen balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
3
30
0
1
Order By: Relevance
“…The amplitude and breadth of the transcriptome response were dose responsive, suggesting the quantity of ingested protein and leucine could be mechanistically instrumental in muscle recovery processes. While much remains to be learnt about the benefit, harm, accentuating, or modulating nature of inflammatory processes in skeletal muscle and the effects of amino acids thereon, the present immune-myogenic molecular programming suggests protein-leucine feeding may complement increased myofibrillar protein synthesis and turnover to support a number of tissue processes responsible for functional recovery, remodeling, and improved subsequent performance phenotype under some conditions (42,47,48,60,66). These findings provide a platform for further research to characterize the functional dose of fed protein/amino acids on myeloid, satellite, and myofibril protein-level cellular molecular responses putatively involved in skeletal muscle regeneration and functional plasticity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amplitude and breadth of the transcriptome response were dose responsive, suggesting the quantity of ingested protein and leucine could be mechanistically instrumental in muscle recovery processes. While much remains to be learnt about the benefit, harm, accentuating, or modulating nature of inflammatory processes in skeletal muscle and the effects of amino acids thereon, the present immune-myogenic molecular programming suggests protein-leucine feeding may complement increased myofibrillar protein synthesis and turnover to support a number of tissue processes responsible for functional recovery, remodeling, and improved subsequent performance phenotype under some conditions (42,47,48,60,66). These findings provide a platform for further research to characterize the functional dose of fed protein/amino acids on myeloid, satellite, and myofibril protein-level cellular molecular responses putatively involved in skeletal muscle regeneration and functional plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the design was a randomized single-blind triple crossover. Following preliminary tests to determine V O2 max and Wmax (42), participants completed a familiarization trial of the 100 min loading cycle exercise. Subsequently, physical activity and diet were standardized for 4.5 days prior to a 2-day period of full dietary control preceding each experimental testing day.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have tested the effects of protein supplementation on endurance performance and recovery in trained athletes beyond the subsequent exercise session (Hill et al, 2013;Nelson et al, 2012;Skillen et al, 2008;Thomson et al, 2011;Witard et al, 2011). No effects on time to exhaustion (TTE) (Hill et al , 2013), running performance and cycling sprint performance (Nelson et al, 2012) at the end of a training period have been reported, whereas others have reported an attenuation of the reduction in TTE www.IJSNEM-Journal.com ORIGINAL RESEARCH (Skillen et al, 2008) or performance in time trials toward the end of intensive endurance training periods (3 to 14 days) compared with isocaloric carbohydrate supplementation.…”
mentioning
confidence: 99%
“…No effects on time to exhaustion (TTE) (Hill et al , 2013), running performance and cycling sprint performance (Nelson et al, 2012) at the end of a training period have been reported, whereas others have reported an attenuation of the reduction in TTE www.IJSNEM-Journal.com ORIGINAL RESEARCH (Skillen et al, 2008) or performance in time trials toward the end of intensive endurance training periods (3 to 14 days) compared with isocaloric carbohydrate supplementation. Only one of the prolonged studies with protein supplementation included runners .…”
mentioning
confidence: 99%